Currently recognized clinically relevant and known genes for human reproduction and related infertility with representation on high-resolution chromosome ideograms - Butler, Merlin G. (Gene, 2015)
OBJECTIVE: To provide an update of currently recognized clinically relevant candidate and known genes for human reproduction and related infertility plotted on high resolution chromosome ideograms (850 band level) and represented alphabetically in tabular form. METHOD: Descriptive authoritative computer-based website and peer-reviewed medical literature searches used pertinent keywords representing human reproduction and related infertility along with genetics and gene mutations. A master list of genes associated with human reproduction and related infertility was generated with a visual representation of gene locations on high resolution chromosome ideograms. GeneAnalytics pathway analysis was carried out on the resulting list of genes to assess underlying genetic architecture for infertility. RESULTS: Advances in genetic technology have led to the discovery of genes responsible for reproduction and related infertility. Genes identified (N = 371) in our search primarily impact ovarian steroidogenesis through sex hormone biology, germ cell production, genito-urinary or gonadal development and function, and related peptide production, receptors and regulatory factors. CONCLUSIONS: The location of gene symbols plotted on high resolution chromosome ideograms forms a conceptualized image of the distribution of human reproduction genes. The updated master list can be used to promote better awareness of genetics of reproduction and related infertility and advance discoveries on genetic causes and disease mechanisms.